2022
DOI: 10.3390/foods11162461
|View full text |Cite
|
Sign up to set email alerts
|

Widely Targeted Metabolomics Profiling Reveals the Effect of Powdery Mildew on Wine Grape Varieties with Different Levels of Tolerance to the Disease

Abstract: Powdery mildew is an economic threat for viticulture because it not only affects grape yield, but also causes a series of impacts on the qualities of fruit and wine, especially the flavors and various metabolites. Different grape varieties may have different levels of powdery mildew resistance/tolerance and their components of their metabolome are also various. In this study, two wine grape varieties, Guipu No.6 (GP6) and Marselan (Mar) with different levels of powdery mildew tolerance, were used to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…The number of metabolites obtained using the widely targeted metabolomics approach is generally between 200 and 1000, which is very important for studying the characteristics of the metabolite components of different varieties. In 2022, a total of 774 metabolites were detected using the widely targeted metabolomics approach in two wine grape varieties, and there were 157 types of flavonoids in 400 secondary metabolites [22]. In the present study, 1062 metabolites were detected in summer and winter 'Kyoho' grapes, including 285 flavonoids, 129 phenolic acids, 122 lipids, 108 amino acids and derivatives, 66 organic acids, 58 alkaloids, 54 nucleotides and derivatives, 52 terpenes, 28 tannins, and 26 lignans and coumarins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of metabolites obtained using the widely targeted metabolomics approach is generally between 200 and 1000, which is very important for studying the characteristics of the metabolite components of different varieties. In 2022, a total of 774 metabolites were detected using the widely targeted metabolomics approach in two wine grape varieties, and there were 157 types of flavonoids in 400 secondary metabolites [22]. In the present study, 1062 metabolites were detected in summer and winter 'Kyoho' grapes, including 285 flavonoids, 129 phenolic acids, 122 lipids, 108 amino acids and derivatives, 66 organic acids, 58 alkaloids, 54 nucleotides and derivatives, 52 terpenes, 28 tannins, and 26 lignans and coumarins.…”
Section: Discussionmentioning
confidence: 99%
“…The sample extracts were analyzed using an LC-ESI-MS/MS system (HPLC: Shimpack UFLC Shimadzu CBM30A system, www.shimadzu.com.cn/, accessed on 2 September 2021; MS: Applied Biosystems 6500 Q TRAP, www.appliedbiosystems.com.cn/, accessed on 2 September 2021). The 24 grape samples were analyzed under the following UPLC conditions based on a previous report [22]: column, Agilent SB-C18 (1.8 µm, 2.1 mm × 100 mm). The components of mobile phase A were 0.1% formic acid and pure water.…”
Section: Uplc Conditionsmentioning
confidence: 99%
“…These findings indicate that the defense mechanisms of Zhongzhe 1 sugarcane may not be associated with phenylpropanoid metabolism. Unlike studies on the defense mechanism of grape plants against powdery mildew, Yu’s study [ 49 ] found that the defense mechanism of grape varieties after powdery mildew infection may be related to phenylalanine metabolism. These findings suggested that different-resistant plants may have different defense mechanisms against microorganisms.…”
Section: Discussionmentioning
confidence: 97%
“…Recent research has increasingly shown in various economically significant plants that flavonoids play an integral role in plant resistance to powdery mildew, positioning them as key substances in combating this disease ( Yu et al., 2022 ; Xu et al., 2023 ). When E. lonicerae invades honeysuckle, it initially confronts the direct or indirect defense mechanisms presented by these abundant flavonoids.…”
Section: Discussionmentioning
confidence: 99%